Preferential import of queuosine-modified tRNAs into Trypanosoma brucei mitochondrion is critical for organellar protein synthesis - Kulkarni, Sneha; Rubio, Mary Anne T; Hegedűsová, Eva; Ross, Robert L; Limbach, Patrick A; Alfonzo, Juan D; Paris, Zdeněk (Nucleic acids research, 2021)
Transfer RNAs (tRNAs) are key players in protein synthesis. To be fully active, tRNAs undergo extensive post-transcriptional modifications, including queuosine (Q), a hypermodified 7-deaza-guanosine present in the anticodon of several tRNAs in bacteria and eukarya. Here, molecular and biochemical approaches revealed that in the protozoan parasite Trypanosoma brucei, Q-containing tRNAs have a preference for the U-ending codons for asparagine, aspartate, tyrosine and histidine, analogous to what has been described in other systems. However, since a lack of tRNA genes in T. brucei mitochondria makes it essential to import a complete set from the cytoplasm, we surprisingly found that Q-modified tRNAs are preferentially imported over their unmodified counterparts. In turn, their absence from mitochondria has a pronounced effect on organellar translation and affects function. Although Q modification in T. brucei is globally important for codon selection, it is more so for mitochondrial protein synthesis. These results provide a unique example of the combined regulatory effect of codon usage and wobble modifications on protein synthesis; all driven by tRNA intracellular transport dynamics.
Keywords: konformace nukleové kyseliny; Nucleoside Q; cytoplazma; nukleosid Q; RNA Processing, Post-Transcriptional; RNA, Transfer; guanosin; Guanosine; Anticodon; mitochondrie; RNA transferová; Protein Biosynthesis; Cytoplasm; Trypanosoma brucei brucei; posttranskripční úpravy RNA; buněčné jádro; Cell Nucleus; Nucleic Acid Conformation; Codon; antikodon; kodon; proteosyntéza; Mitochondria